Regulation of synaptic plasticity by astroglia - Rusakov, Dmitri (Henry Stewart Talks, 2012)
Astroglia are the most abundant type of glial cells, Their role has recently emerged as an active contributor to neural function, The underlying mechanisms remain poorly understood, Astrocytes release D-serine in a Ca2+ dependent manner, Interference with this release reduces activation of synaptic NMDA receptors, This in turn could severely impair induction of long-term synaptic potentiation, Astroglia thus may play a fundamental role in mechanisms of memory formation in the brain